PERAN MASA BER KB DALAM MEMEDIASI PENGARUH FAKTOR EKONOMI, SOSIAL DAN DEMOGRAFI TERHADAP JUMLAH ANAK PADA PASANGAN USIA SUBUR DI KABUPATEN BADUNG - nuryati, Agung PUTRI; yasa, i g w murjana (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME 04.NO.10.TAHUN 2015, 2016)
Control of high population growth rate can be done by regulating and controlling birth. Family Planning (FP) invites couples of fertile age (CFA) to regulate birth by means of tools, drugs, and contraceptive methods. This study is a quantitative associative study aimed to analyze influence of family income, age of wife’s first marriage, wife’s education, wife’s working hours, and period of joining family planning program on the number of children in couples of childbearing age in Badung District, also to analyze the effect of indirect factors of family income, age of wife’s first marriage, wife’s education and wife’s working hours on the number of children in couples of childbearing age in Badung District through a period of family planning. The number of samples were taken from 203 CFA through the interview method. Analysis technique used was path analysis. The results showed that the variables of family income and wife’s working hours had positively significant effect on future family planning, while the age of first marriage wife had a negatively significant effect and wife’s education had a negatively significant effect on the period of family planning. The indirect effect of income and wife’s education through joining the period of family planning program was positively significant on the number of children born alive, while age of wife’s first marriage and wife’s working hours had a negatively significant effect on the number of children born alive through a period of family planning in couples of childbearing age in Badung District. To reduce the number of births age of wife’s first marriage should be increased, improving wife’s education programs by socializing Gen-Re (Generation Planning) program and increasing the family income to better finance the children's lives so that the younger generations are born healthy and well educated.
Keywords: Economic Factors, Social and Demographics, Period of Family Planning, Number of Children, Couples of Fertile Age.